ҒАФУР ҒУЛОМ НАСРИДА ТАСВИР ВА ИФОДАНИНГ ЎЗИГА ХОСЛИГИ - Муратова, Г. (SCIENCE and SOCIETY, 2024)
This article examines the means of artistic imagery in the prose works of G. Ghulom. The author’s stories "Netay" and "Shum Bola" are analyzed in it. Certain conclusions about G.Ghulam’s maturity as a writer are expressed through pictorial means such as portraits and landscapes in these stories.